Remaking bioethics’ history in Latin America. James Drane’s contribution? - Lolas Stepke, Fernando (Acta Bioethica, 2005)
This article presents the person and work of James Drane in their relation to bioethics in Latin America. After a brief analysis of his career and publications, the establishment of a study center at the Edinboro University of Pennsylvania is underscored, a legacy of the late Russell B. Roth and his family, which will perpetuate the spirit of free inquiry and loyalty to his principles that Drane has kept throughout his life.